NIVELES SÉRICOS REFERENCIALES DE UREA, CREATININA Y ANÁLISIS FÍSICO-QUÍMICO DE LA ORINA EN Saimiri boliviensis - Arias Ch., Henry (2002)
The purpose of the study was to establish reference values for serum urea and creatinine, and for physical and chemical analysis in urine in Saimiri boliviensis. Fifteen females and 15 males raised in captivity at the Centro de Reproducción y Conservación de Primates No Humanos, Iquitos, Peru were used. Mean values of urea and creatinine were 66.7 ± 25.2 and 2.0 ± 0.5 respectively, and without statistical differences between sexes. Mean values forpH was 6.9 ± 0.7 and for specific gravity was 1.021±0.004. Urea and creatinine values were higher to those reported for Aotus nancymae.